'If drugs does that to you, then I don't want it.' Resiliency among non-marijuana using adolescents. (20th October 2016) - Gilliard-Matthews, Stacia; Stevens, Robin; Medina, Michael
ABSTRACT: The current study utilizes an asset-based approach to examine inner-city African-American and Latino adolescent non-marijuana use. Interview findings suggest that the common theme in adolescent narratives is why they avoid marijuana use. Specifically, adolescents formulate several reasons situated in their perceptions of self, peers, and parents to avoid marijuana use. Drawing on resiliency theory and to broaden our scope of inquiry, we utilize these findings to further delve into the relationship between perceptions of self, peer communication, parental monitoring, and marijuana use avoidance utilizing survey data analysis. Findings can be used to leverage prevention programs with this population.